Evaluatıon Of Occlusal Adjustment After Orthodontıc Treatment Wıth Sam Iı Artıculator And T-Scan System - Gökhan Önçağ; Servet Doğan; Münire Ece Sabah; Ahmet Saraçoğlu; Birgül Özpınar (Galenos Yayinevi, 2000)
The aim of orthodontic treatment today has been expanded to include the ideal skeletal and functional relationships. This study was conducted on 9 girls and 11 boys, (total 20) between 13-15 years of age. The patients were evaluated 6 months into retention with the T-Scan occlusal analyzer and semi-adjustable SAM II articulator following non-extraction treatment with Straight Wire Roth technique. The number and localisation and the time and amount of premature contacts were evaluated qualitative and quantitatively in this study, in patients with ideal occlusion at the end of orthodontic treatment. The results of our study indicate the importance of apropriate selective grinding of primary contacts, for the stability of orthodontic treatment.